Interpreting Strategic Costing Management Based on the Awareness of Muslim Entrepreneurs: A Phenomenological Study - Kurniawan, Lalu Martahadi Trisna; Sokarina, Ayudia (Formosa Journal of Science and Technology, 2024)
This study aims to understand the implementation of strategic costing in alignment with Islamic values among Muslim entrepreneurs. Muslim entrepreneurs who pursue Falah business goals—achieving social, economic, and spiritual well-being—must possess a deep awareness of Islamic values that reflect ethical practices in their business operations. This research uses a phenomenological approach as its methodology. Data collection was carried out through interviews with Muslim entrepreneurs in Mataram City. The findings reveal that the application of Islamic concepts in current business practices is still lacking. Therefore, as one of the regions in Indonesia with a Muslim majority, it is important to explore how Muslim entrepreneurs in Mataram City implement contemporary strategic costing in accordance with Islamic business values.